Interference effects of aircraft on earth's electromagnetic response at very low frequency and low frequency. (29th September 2014) - Shan, C.; Pedersen, L. B.
ABSTRACT Over the last few decades, very low frequency electromagnetics has been widely and successfully applied in mineral exploration and groundwater exploration. Many radio transmitters with strong signal‐to‐noise ratios are scattered in the very low frequency band and low frequency band. Based on experiences gained from ground measurements with the radio‐magnetotelluric technique operating in the frequency interval 1–250 kHz, broadband magnetometers have been used to cover both very low frequency (3–30 kHz) and low frequency (30–300 kHz) bands to increase the resolution of the near‐surface structure. The metallic aircraft as a conductive body will distort the magnetic signal to some extent, and thus it is important to investigate aircraft interference on the electromagnetic signal. We studied noise caused by rotation of an aircraft and the aircraft itself as a metallic conductive body with three methods: 3D wave polarization, determination of transmitter direction and full tipper estimation. Both very low frequency and low frequency bands were investigated. The results show that the magnetic field is independent of the aircraft at low frequencies in the very low frequency band and part of the low frequency band (below 100 kHz). At high frequencies (above 100 kHz), the signals are more greatly influenced by the aircraft, and the wave polarization directions are more scattered, as observed when the aircraft turned. Some aircraft generated noise mixed with radio transmitter signals, detected as 'dummy' signals by the 3D wave polarization method. The estimated scalar magnetic transfer functions are dependent on the aircraft flight directions at high frequencies, because of aircraft interference. The aircraft eigenresponse in the transfer functions (tippers) between vertical and horizontal magnetic field components was compensated for in the real part of the estimated tippers, but some unknown effect was still observed in the imaginary parts.